2022
DOI: 10.1140/epjp/s13360-022-02579-w
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer enhancement of magnetized nanofluid flow due to a stretchable rotating disk with variable thermophysical properties effects

Abstract: Ferrofluid is a one-of-a-kind substance that functions both as a magnetic solid and as a liquid. In this article, waterbased Fe3O4 and Mn-ZnFe2O4 nanofluids between parallel stretchable spinning discs are considered. To carry out the study, the influence of rotational viscosity in the flow, which is due to the difference in rotation between the fluid and magnetic particles, and the applied magnetic field are examined. Additional impacts incorporated to the novelty of the model are the variable viscosity and va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…This refers to how fluids behave when they come into contact with solid boundaries and can affect the rate at which the fluid moves near the surface. The extent of the slip is directly related to the amount of shear stress experienced by the fluid at the boundary 75 , 76 . This understanding is crucial for accurately analyzing heat transfer through convection.…”
Section: Flow Model Of the Problemmentioning
confidence: 99%
“…This refers to how fluids behave when they come into contact with solid boundaries and can affect the rate at which the fluid moves near the surface. The extent of the slip is directly related to the amount of shear stress experienced by the fluid at the boundary 75 , 76 . This understanding is crucial for accurately analyzing heat transfer through convection.…”
Section: Flow Model Of the Problemmentioning
confidence: 99%
“…Consequently, as a result of the challenge of effectively increasing heat transfer, reducing thermal load, and boosting system effectiveness in several industrial and technical applications, including solar energy storage, mixing operations, food processing technology, drying chambers, coating processes, and microelectronic device cooling, there have been enormous research contributions on the numerical study of mixed convection flow in enclosures subjected to differential heating conditions 10–14 …”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Consequently, as a result of the challenge of effectively increasing heat transfer, reducing thermal load, and boosting system effectiveness in several industrial and technical applications, including solar energy storage, mixing operations, food processing technology, drying chambers, coating processes, and microelectronic device cooling, there have been enormous research contributions on the numerical study of mixed convection flow in enclosures subjected to differential heating conditions. [10][11][12][13][14] Using two magnetic field configurations, thermomagnetic convection and entropy analysis in a ferrofluid-filled cubical cavity with a cylindrical heat source, as well as magnetohydrodynamic (MHD) mixed convection flow and heat transfer of a Cu-water nanofluid in a square cavity filled with a porous media, have been studied. 15,16 The results demonstrate that both designs significantly improve cooling, with the double-Halbach array configuration performing somewhat better.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al 34 used von Karman's radiative hydromagnetic nanofluid flow between two coaxial rotating porous discs to generate entropy. On a linear permeable stretched surface, Gangadhar et al [36][37][38][39][40][41] explored the formation of entropy and the application of an angled magnetic field to Williamson nanoliquid. Recent research on the flow of nanofluids with different flow characteristics may be found in.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research on the flow of nanofluids with different flow characteristics may be found in. [36][37][38][39][40][41] The nonlinear Casson-Maxwell liquid between two porous discs using the Buongiorno theory, using extra impacts of nonlinear heat transfer and chemical reactions, has yet to be researched, according to the literature review. The essential transformations are used to convert nonlinear coupled expressions to ordinary differentials.…”
Section: Introductionmentioning
confidence: 99%